THE USE OF DIGITAL INFLUENCERS BY BRAZILIAN TOURISTS TO CHOOSE TOURIST DESTINATIONS ABROAD: A PROPOSAL USING THE TECHNOLOGY ACCEPTANCE MODEL – TAM - Frederico Fagundes de Lima Andrade, Daniel; Cassiano de Medeiros, Fernando (Revista Gênero e Interdisciplinaridade, 2023)
This theoretical article aims to propose a new research model, using the constructs of the Technology Acceptance Model ((Technology Acceptance Model – TAM) to analyze the influence generated by Digital Influencers through the social media Instagram in the choice of International Tourist Destinations by Brazilian Tourists. It will be a research proposal to demonstrate that there is an influence in the choice of international tourist destinations generated by Instagram stories and feeds.